Evidence-based green algal genomics reveals marine diversity and ancestral characteristics of land plants. (December 2016) - van Baren, Marijke; Bachy, Charles; Reistetter, Emily; Purvine, Samuel; Grimwood, Jane; Sudek, Sebastian; Yu, Hang; Poirier, Camille; Deerinck, Thomas; Kuo, Alan; Grigoriev, Igor; Wong, Chee-Hong; et al.
Abstract Background Prasinophytes are widespread marine green algae that are related to plants. Cellular abundance of the prasinophyteMicromonas has reportedly increased in the Arctic due to climate-induced changes. Thus, studies of these unicellular eukaryotes are important for marine ecology and for understanding Viridiplantae evolution and diversification. Results We generated evidence-basedMicromonas gene models using proteomics and RNA-Seq to improve prasinophyte genomic resources. First, sequences of four chromosomes in the 22 MbMicromonas pusilla (CCMP1545) genome were finished. Comparison with the finished 21 Mb genome ofMicromonas commoda (RCC299; named herein) shows they share ≤8, 141 of ~10, 000 protein-encoding genes, depending on the analysis method. Unlike RCC299 and other sequenced eukaryotes, CCMP1545 has two abundant repetitive intron types and a high percent (26 %) GC splice donors.Micromonas has more genus-specific protein families (19 %) than other genome sequenced prasinophytes (11 %). Comparative analyses using predicted proteomes from other prasinophytes reveal proteins likely related to scale formation and ancestral photosynthesis. Our studies also indicate that peptidoglycan (PG) biosynthesis enzymes have been lost in multiple independent events in select prasinophytes and plants. However, CCMP1545, polarMicromonas CCMP2099 and prasinophytes from other classes retain the entire PG pathway, like moss and glaucophyte algae. Surprisingly, multiple vascular plants also have the PG pathway, except the Penicillin-Binding Protein, and share a unique bi-domain protein potentially associated with the pathway. AlongsideMicromonas experiments using antibiotics that halt bacterial PG biosynthesis, the findings highlight unrecognized phylogenetic complexity in PG-pathway retention and implicate a role in chloroplast structure or division in several extant Viridiplantae lineages. Conclusions Extensive differences in gene loss and architecture between related prasinophytes underscore their divergence. PG biosynthesis genes from the cyanobacterial endosymbiont that became the plastid, have been selectively retained in multiple plants and algae, implying a biological function. Our studies provide robust genomic resources for emerging model algae, advancing knowledge of marine phytoplankton and plant evolution.